2022
DOI: 10.3390/bios12100812
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Morphological Traits of Leaves for Urban Tree Selection for Air Pollution Biomonitoring: A Review

Abstract: Urban trees provide different ecosystem benefits, such as improving air quality due to the retention of atmospheric particulate matter (PM) on their leaves. The main objective of this paper was to study, through a systematic literature review, the leaf macro-morphological traits (LMTs) most used for the selection of urban trees as air pollution biomonitors. A citation frequency index was used in scientific databases, where the importance associated with each variable was organized by quartiles (Q). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Banja Luka and Prijedor were characterized by the maximal average values of most traits of the leaf blade samples. Such data can be explained by the effects of most common aero pollutants, including CO, SO 2 , NO 2 , PM 10 on the morphological traits of the leaves of urban trees (Corada et al, 2021;Rodríguez-Santamaría et al, 2022). Data taken from the Hydrometeorological Institute of the Republic of Srpska showed that average annual concentration of main air pollutants did not exceed maximal annual values, except Doboj, where concentration of particulate matter was above the limit level in 2019 when the samples were collected.…”
Section: Results / Rezultatimentioning
confidence: 99%
“…Banja Luka and Prijedor were characterized by the maximal average values of most traits of the leaf blade samples. Such data can be explained by the effects of most common aero pollutants, including CO, SO 2 , NO 2 , PM 10 on the morphological traits of the leaves of urban trees (Corada et al, 2021;Rodríguez-Santamaría et al, 2022). Data taken from the Hydrometeorological Institute of the Republic of Srpska showed that average annual concentration of main air pollutants did not exceed maximal annual values, except Doboj, where concentration of particulate matter was above the limit level in 2019 when the samples were collected.…”
Section: Results / Rezultatimentioning
confidence: 99%